Educational Content Creation and Sharing by Low-Income Visually Impaired People in India - Vashistha, Aditya; Brady, Erin; Thies, Bill; Cutrell, Ed (ACM - Association for Computing Machinery, 2014)
Low-income visually impaired people face a wide variety of educational challenges which are magnified in the developing world. Digital assistive technologies (such as screen readers) are typically out of reach, so individuals depend on Braille and audio recordings to access educational content. Unfortunately, there are acute shortages of Braille and high quality audio books for many subjects, leaving students scrambling for ways to continue their education. We present a formative study that examines the educational landscape for low-income visually impaired communities in rural and peri-urban India, the challenges they face in accessing educational content, and the solutions they have invented. We conducted interviews with 16 stakeholders, including students, teachers, and content producers, to understand the education ecosystem in their communities and how they use technologies such as basic mobile phones to consume, create, and share educational content. In particular, we found that these communities have established an informal network of peer-produced audio content that is shared via Bluetooth, memory cards and CDs. Our analysis suggests ways in which technology can improve access to professionally authored materials and augment these informal networks of peer-production.